2009
DOI: 10.1007/s10531-009-9659-6
|View full text |Cite
|
Sign up to set email alerts
|

Lichen diversity and composition in Araucaria forests and tree monocultures in southern Brazil

Abstract: Tree plantations for commercial use have been replacing native ecosystems all over the world. We investigated how forest conversion to plantations of exotic and native tree species may influence lichen diversity and composition in a southern Brazilian landscape. The lichen community from the National Forest of São Francisco de Paula was studied using three stands of each of the four vegetation types: native Araucaria forest and plantations of Araucaria, Pine and Eucalyptus trees. All plantation stands were sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
1
13
0
6
Order By: Relevance
“…Species from the genus Parmotrema were largely abundant in forest plantations. Only 5.7% of Parmeliaceae species were recorded in the native Araucaria forest environment; the greater representativeness of the family Parmeliaceae found in this study corroborates other studies carried out in native Araucaria forest areas in Rio Grande do Sul (Fleig & Grüninger 2000;Käffer & Martins -Mazzitelli 2005;Käffer et al 2009). …”
Section: Sticta Weigelii Xsupporting
confidence: 91%
“…Species from the genus Parmotrema were largely abundant in forest plantations. Only 5.7% of Parmeliaceae species were recorded in the native Araucaria forest environment; the greater representativeness of the family Parmeliaceae found in this study corroborates other studies carried out in native Araucaria forest areas in Rio Grande do Sul (Fleig & Grüninger 2000;Käffer & Martins -Mazzitelli 2005;Käffer et al 2009). …”
Section: Sticta Weigelii Xsupporting
confidence: 91%
“…Most studies carried out in conservation unities using lichens report the changes in forest areas, especially related to management practices (Käffer et al 2009, Giordani et al 2012, Boudreault et al 2013, Király et al 2013) and habitat fragmentation (Tuvi et al 2011. In our study, the changes observed in different forest areas are especially related to the management made in the area, due to the presence of cattle and sheep.…”
Section: Discussionmentioning
confidence: 54%
“…Most studies carried out on lichens aiming at evaluating the conservation stage in forest environments (Lidén et al 2004, Cáceres et al 2007, 2008, Käffer et al 2009, Tuvi et al 2011, Boudreault et al 2013, Hauck et al 2013, Estrabou et al 2014 are based on the evaluation of species richness and diversity and/or on key species from preserved environments. Thus, our hypothesis is that lichen community occurring in riparian forest areas in an environmental protection area (EPA of Ibirapuitã) may indicate the environmental quality of these regions, mapping better areas for lichen development by using the index of atmospheric purity (IAP) (Le Blanc and De Sloover 1970) with the environmental classification factor (ECF) as the correction factor, proposed by Käffer et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…El cambio en el uso del suelo y el remplazo de los bosques nativos por plantaciones de coníferas trae consigo fuertes repercusiones que afectan la calidad del suelo, la circulación tanto de nutrientes como de agua, además de la dinámica de las poblaciones de plantas y animales que habitan estos ecosistemas (Barlow et al, 2007;Calviño-Cancela, Rubido-Bará y van Etten, 2012;Goward y Arsenault, 2000;Hietz-Seifert, Hietz y Guevara, 1996), debido a que se homogenizan las condiciones ambientales, como luz y humedad, acidez y rugosidad de los árboles a nivel local, con lo que se suprime la variedad de microecosistemas ofrecida por los bosques naturales (Käffer, Ganade y Marcelli, 2009;Ardila, Moncada y Lücking, 2015).…”
Section: Introductionunclassified